Uma luta pelo reconhecimento do trabalho contra a política de redução de pessoal - Leda Leal Ferreira (Universidade do Porto, 2011)
The text presents the results of a study developed 20 years ago by the author in light of the concept of "recognition of work" according to the psychodynamics of work. This study was the first of a series of other works that followed in the next 15 years related to the struggle of petroleum workers against the "enxugamento de pessoal" policy, the Brazilian version of downsizing. A policy applied in the 1990s by the company management in the wake of a policy known as productive restructuring which was widely adopted by Brazilian and international firms and particularly by the petroleum sector.